SYSTEM-SYNERGETIC DIAGNOSTIC READINESS OF FUTURE SPECIALISTS OF AVIATION TO THE PROFESSION - Лузік, Е. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article deals with the problem of professional preparedness of future specialists in universities aviation industry using the criteria of system modeling educational process – invariants didactic elements of learning activities